Pengaruh Rangsangan Tertawa Terhadap Penyelesaian Block Design Test - siti qodariah; lelywati Idham suryana; Vita Latifah (SCHEMA (Journal of Psychological Research), 2011)
Education systems in the Faculty of Psychology Unisba quite heavy and tight especially in semester V. The pressures and demands could reduce the ability in learning the material and complete the study.. Pressures and demands can affect the emotions of students, it cause less efficient and effective in solving the problem.  Therefore it is necessary to design an intervention that take the practically, energy or cost efficiency, so it does not create a new problem for students. In the current study, researchers wanted to give stimulation of laugh. The method of research is experimental design by using Randomized Two Group Design. With stimulation of laugh as an Independent Variable and Solve the Block Design Test (analogy of the problem) as the Dependent Variable. The sample is students of the Faculty of Psychology Unisba semester V, with Purposive Sampling technique. The results is the stimulation of laugh can affect the ability to solve the Block Design Test, that is stimulation of laugh can accelerate the ability to solve problems in academic or social.